Inside Cover: Fabclavines: Bioactive Peptide–Polyketide‐Polyamino Hybrids from Xenorhabdus (ChemBioChem 4/2014). Issue 4 (3rd March 2014) - Fuchs, Sebastian W.; Grundmann, Florian; Kurz, Michael; Kaiser, Marcel; Bode, Helge B.
<x xml:space="preserve">Abstract</x> The inside cover picture shows a "fabclavine" produced by two entomopathogenic Xenorhabdus bacteria (background). H. B. Bode et al. elucidated its structure and biosynthesis (p. 512 ff.) and show that fabclavines might serve as toxins against insect cells or subsequently protect the insect cadaver (here Manduca sexta) against various competitors, including bacteria, fungi, and protozoa. Graphical assistance by F. A. Fuchs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>